STATISTICAL, CLINICAL AND MORPHOLOGICAL CLASSIFICATIONS OF CORONARY HEART DISEASE — POSSIBLE TO UNITE? - S. A. Boytsov; I. V. Samorodskaya; A. S. Galyavich; F. I. Belyalov; D. Sh. Vaisman; I. S. Yavelov; N. N. Nikulina; S. S. Yakushin; O. V. Zayratiants; E. P. Kakorina (Российский кардиологический журнал, 2017)
A problem of synonymy and synonyms legitimation is of big importance in practice, as multiple classifications lead to problems of organization and provision of medical care, and incorrect statistics. The article is a consensus of experts on the issue of agreement/implementation of clinical classifying of synonyms of terms listed in ICD-10, agreement on the modern clinical and morphological terms.